1999
DOI: 10.1128/.67.4.1633-1639.1999
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Enhances the Production of Vascular Endothelial Growth Factor by Human Pulp Cells in Culture

Abstract: We investigated whether vascular endothelial growth factor (VEGF) production by human pulp cells (HPC) is regulated by lipopolysaccharide (LPS) in relation to the pathogenesis of pulpitis. Although HPC incubated with medium alone only marginally expressed VEGF mRNA and produced a low level of VEGF as detected by enzyme-linked immunosorbent assay, the VEGF mRNA expression and VEGF production were markedly enhanced upon stimulation with LPS from Escherichia coli. Prevotella intermedia LPS, phorbol 12-myristate 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
3
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 8 publications
4
26
3
2
Order By: Relevance
“…We observed that odontoblast-like cells and macrophages, but not undifferentiated pulp cells, exposed to bacterial LPS consistently upregulate VEGF synthesis. While the results obtained from cell lines should be interpreted with caution, our experiments confirmed a previous report that demonstrated that VEGF was up-regulated in a mixed population of human dental pulp cells exposed to LPS (27), and suggest that odontoblasts and macrophages may be the cell populations responsible, in part, for the previously reported upregulation of VEGF expression induced by LPS.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed that odontoblast-like cells and macrophages, but not undifferentiated pulp cells, exposed to bacterial LPS consistently upregulate VEGF synthesis. While the results obtained from cell lines should be interpreted with caution, our experiments confirmed a previous report that demonstrated that VEGF was up-regulated in a mixed population of human dental pulp cells exposed to LPS (27), and suggest that odontoblasts and macrophages may be the cell populations responsible, in part, for the previously reported upregulation of VEGF expression induced by LPS.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, 0-20 lg ml )1 E. coli LPS or 0-80 lg ml )1 P. intermedia LPS were used to challenge the cells. Other studies have used a range of 0.01-100 lg ml )1 LPS (27,44), which is believed to be within a range of LPS relevant to pulp pathologies (45). A previous investigation has evaluated the effect of LPS from Porphyromonas endodontalis, Porphyromonas gingivalis, Fusobacterium nucleatum, and E. coli on DNA content, protein synthesis, and alkaline phosphatase activity in dental pulp cells (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipopolysaccharide activates the NF-jB and MAPK/AP-1 signaling pathways and their associated inflammatory gene expression in fibroblasts, including human gingival fibroblasts (24,43). However, lipopolysaccharide activation of AP-1 in human gingival fibroblasts is controversial, and Jin et al recently reported that in normal human gingival fibroblasts, Escherichia coli lipopolysaccharide stimulated NF-jB, but not AP-1 (45,46). The IL-6 gene promoter is under the regulation of AP-1 and NF-jB, and can contain binding sites for other transcription factors in some types of cells (47,48); both AP-1 and NF-jB are involved in IL-1-stimulation of IL-6 in human gingival fibroblasts (13,24,47,49).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the increase of VEGF expression is consistent with enhanced vascularization during dental pulp inflammation (Tran-Hung et al 2006). The dental pulp cells can also produce VEGF in response to lipopolysaccharide (LPS; Matsushita et al 1999) and pro-inflammatory cytokines such as interleukin (IL)-1 (Chu et al 2004). These previous reports suggested that dental pulp cells play a role in the aetiology of pulpitis through the production of VEGF.…”
Section: Introductionmentioning
confidence: 99%